2023
DOI: 10.3389/fpubh.2023.1113255
|View full text |Cite
|
Sign up to set email alerts
|

Activity diversity is associated with the prevention of frailty in community-dwelling older adults: The Otassha Study

Abstract: IntroductionA prior study showed an association between diversity in daily activities (type, frequency, evenness) and frailty in older adults. However, the causality of this relationship is unclear. Therefore, this study aimed to clarify the relationship between activity diversity and frailty through a 2-year longitudinal study conducted among community-dwelling older adults.MethodsWe evaluated data from the 2018 and 2020 waves of the Otassha Study. Frailty was assessed using the Cardiovascular Health Study cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Activity diversity denotes the variety of activity types that people engage in during a particular time frame. It has been shown that activity diversity is associated with higher cognitive functioning ( Brown et al, 2023 ), more agreeable personality states ( Lindner et al, 2023 ), and lower likelihood to develop frailty ( Takahashi et al, 2023 ) and depression ( Lee, Yu, et al, 2018 ).…”
mentioning
confidence: 99%
“…Activity diversity denotes the variety of activity types that people engage in during a particular time frame. It has been shown that activity diversity is associated with higher cognitive functioning ( Brown et al, 2023 ), more agreeable personality states ( Lindner et al, 2023 ), and lower likelihood to develop frailty ( Takahashi et al, 2023 ) and depression ( Lee, Yu, et al, 2018 ).…”
mentioning
confidence: 99%